PERAN ORANGTUA PENGIDAP HIV/AIDS TERHADAP PENDIDIKAN ANAK DI KOTA PONTIANAK - Farhadiansyah, Farhadiansyah; Rustiyarso, Rustiyarso; Zakso, Amrazi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research was to find out the role of parents with HIV / AIDS as the motivator, facilitator and mediator to children's education in Pontianak city. The research method applied descriptive research which is in the form of qualitative research. Sample of this research was taken from the parents with HIV and companions suffering HIV. Instrument of data collection in this study was guided observation, guided interview and documentation study. The results proved that: (1) the role of the parents with HIV as motivator to children's education to be categorized well by advising their descendants to frequently have worship, to study harder in school and also to keep the way of associating with social environment. (2) the role of the parents with HIV as facilitators in education was categorized good enough, because the parents have been providing children for certain facilities, such as desks, books, stationery and bags. (3) the role of the parents with HIV as mediators to children's education was categorized good, due to the parents keep involving children to socialize with the community. Keywords: the Role of Parents, HIV / AIDS, Children's Education